MORPHOLOGICAL AND MOLECULAR IDENTIFICATION of ENDOPHYTIC FUNGI FROM PSIDIUM Guajava and Vachellia nilotica - Samaila, Adamu Babayo; Panda, Sam Mao; Barde, Auwal AAlhassan; Tukur, Sani Tajo; Samaila, Aishatu Adamu (FUDMA Journal of Sciences, 2026)
Endophytic fungi are essential components of plant ecosystems, often contributing to host health and secondary metabolites production. The present study aimed to isolate and identify fungal endophytes from the stems and leaves of P. guajava and V. nilotica. Morphological, Molecular and Phylogenetic Identification of were carried out using standard procedures. Fungi were isolated and categorized by host tissue using appropriate fungal atlas. Molecular identification was performed using rRNA sequence analysis (ITS1, 5.8S, ITS2), and phylogenetic relationships were established by comparing sequences against GenBank database matches. A total of 20 endophytic fungi were isolated from four host segments (P. guajava stem (PGS), P. guajava leaves, (PGL), V. nilotica leaves (VNL), V. nilotica stem (VNS) corresponding to a colonization frequency of 80.95%. The following fungal isolates were identified: Thysanophora penicilloides, Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus, Fusarium spp, Sporangia spp, Fusarium verticillioides, Aureobasidium pullulans, and Gliocladium roseum. Psidium guajava leaves (PGL) exhibited the highest colonization (26.19%), followed by its stem (23.80%), while Vachellia nilotica showed lower frequencies (16.66% for leaves and 14.28% for stems). Dominant species identified include: Aspergillus fumigatus, Fusarium verticillioides, Aspergillus flavus, and Aspergillus niger. Molecular analysis of the ITS/rRNA regions confirmed the identity of four primary isolates (PGL, VNL, PGS, VNS) with DNA fragments ranging from 558 to 1056 bp. The DNA fragments show a sequence identity percentages range between 99.77% and 99.99% indicating a high taxonomic accuracy within the respective species clades.